2006
DOI: 10.2337/dc06-0709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Insulin Resistance Among U.S. Adolescents

Abstract: OBJECTIVE -We sought to examine the distribution of insulin and homeostasis model assessment of insulin resistance (HOMA-IR) and associations of HOMA-IR with sex, race/ ethnicity, age, and weight status, as measured by BMI, among U.S. adolescents. Health and Nutrition Examination Survey 1999 -2002, analysis was performed for a nationally representative subsample of 1,802 adolescents without diabetes who had fasting laboratory measurements. The main outcome measure was HOMA-IR, calculated from fasting insulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
294
10
17

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(351 citation statements)
references
References 37 publications
23
294
10
17
Order By: Relevance
“…While numerous cross-sectional studies have noted positive associations ( r = 0.31 to 0.85) between insulin and measures of adiposity in youth, the relationships between change in weight status and change in IR have not been examined thoroughly [28]. The few longitudinal studies of youth have consistently reported that change in weight is positively associated with change in insulin or IR and negatively associated with insulin sensitivity [911].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous cross-sectional studies have noted positive associations ( r = 0.31 to 0.85) between insulin and measures of adiposity in youth, the relationships between change in weight status and change in IR have not been examined thoroughly [28]. The few longitudinal studies of youth have consistently reported that change in weight is positively associated with change in insulin or IR and negatively associated with insulin sensitivity [911].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance was determined with the homeostatic model (HOMA-IR: fasting insulin mmolÂglucose mmol=22.5) (Matthews et al 1985). HOMA-IR values >4.39 were diagnostic for insulin resistance (Lee et al 2006). As done previously (Saito et al 2004), hyperprolactinemia was defined stringently as per our laboratory threshold as >25.4 ng=dL for males and females.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Children suffering from these disorders and symptoms have problems functioning in families, in school, and with their peers. They are also at risk for long-term interpersonal and academic difficulty, legal problems, substance abuse or dependence, and frequent use of social and mental health services (Loeber et al 2000;Ezpeleta et al 2001;Nock et al 2007). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Em virtude de associação entre RI e disfunção endotelial, passo inicial para o processo de aterosclerose (8,9), também tem-se considerado como fator preditor independente de doença cardiovascular (10)(11)(12). Em vários países, a incidência crescente de RI, associada ao aumento das prevalências de obesidade e DM2, tem sido observada (13)(14)(15)(16)(17)(18).…”
unclassified